ANALYSIS OF THE VALUE OF MORAL EDUCATION AND THE MESSAGE OF DA'WAH IN THE NOVEL PULANG BY DARWIS TERE LIYE - Rafid, Reni Haryani; Muhaimi (Four Son Scholarship, 2023)
This study aims to examine and analyze the value of moral education and the messages of Da'wah contained in the novel Darwis Tere Liye “Pulang”. The research method used is descriptive qualitative. The results of research in the novel Pulang by Dervish Tere Liye there are missionary messages conveyed by the author through the content of the story in this novel. The value of moral education that can be taken from the novel “Pulang” is 4 values of moral education. The messages of Da'wah that researchers take from the contents of the story in the novel titled Home is 13 quotes that can be detailed 6 quotes message da'wah Creed, 3 quotes message da'wah Sharia, and 4 quotes message da'wah morals. Then the point that contains faith includes faith in Allah SWT, where this message is included in the message of the creed, then in the contents of the novel entitled Pulang containing a Sharia message that is worship, worship in question here is not to do deeds or actions that are prohibited by Allah and the obligation to seek knowledge, not to mourn a dead person and not grieve over excess when abandoned by a loved one. The last novel titled Pulang also contains moral messages that include morals towards humans and God and morals towards relationships with humans (hablun minnallah wa hablun minannas).